Are University Students Armed with the Necessary Skill Level to Prevent Plagiarism? - Peters, Martine (Canadian Perspectives on Academic Integrity, 2023)
When writing their assignments, university students must search for information online and integrate it into their papers without plagiarizing. They must also support their ideas with references according to their university's standards and requirements. Producing a university assignment thus requires students to use informational skills, academic writing skills, and referencing skills throughout the process. Students are admitted into undergraduate programs with varying levels of mastery of these skills. According to one research, Quebec students expect to develop these skills during their university education, while their professors often expect students to have previously acquired them. Is it possible that this chasm in expectations results in plagiarism because students are not sufficiently prepared? Do universities in other countries face the same situation? This is what we aimed to verify. A quantitative data collection was done in universities in Canada, the United States and in Europe. Two online questionnaires were administered to undergraduate students and professors to obtain information on their use and teaching of informational, writing, and referencing skills. For this presentation, the responses to six specific corresponding questions (students vs faculty) were analyzed: expectation of skill development and level of skills. Since tackling plagiarism at an institutional level requires a shared implication, this analysis will help faculty, administrators, librarians, and tutors to understand students’ experience of the required skills to avoid plagiarism.